Preparation and characterizations of high doping chitosan/MMT nanocomposites films for removing iron from ground water. Issue 1 (February 2021) - Shehap, A.M.; Nasr, R.A.; Mahfouz, Mai A.; Ismail, A.M.
Graphical abstract: Highlights: High Doping Chitosan/MMT Nanocomposites Films were prepared by casting method. The prepared films were characterized using XRD, SEM and FTIR. The highest doping sample (40/ 60 wt%) chitosan/ MMTNPs showed iron removal (89.2 %). The thermodynamic study indicating that the adsorption is spontaneous and endothermic. SEM, EDX and FTIR before and after adsorption process confirmed the adsorption of Fe. Abstract: Chitosan and montmorillonite nanoparticles (MMT NPs) films are prepared using casting method with various weight percentage (10, 20, 30, 40, 50, 60, 70 wt%) of MMT NPs. XRD and FTIR-ATR studies have been conducted to investigate the structural changes for the prepared films. XRD and FTIR-ATR confirmed the existence of interaction between Chitosan and MMTNPs and changing in structure of prepared composite depending upon the percentage of the load MMTNPs in Chitosan. Moreover, the films of high MMT NPs doping are used for the iron adsorption process from ground water. The effect of PH, temperature, adsorbent dose and the initial concentration of adsorbant have been studied. Langumiur and Frendulich are applied to investigate the adsorption process. The adsorption process is aligned with Langumiur isotherm. Fe adsorption process matched with the pseudo first order kinetic Thermodynamics parameters of the adsorption process are calculated indicating that the adsorption process is spontaneous and endothermic. The percent weight ratio (40/60 wt%) chitosan/MMT NPs is found to be the best proper ratio for adsorption of iron which attained 89.2 % at the optimum conditions (1.5 g/L dose, pH 5.5 and 10 mg/L Fe after 210 min). HRSEM, EDX and FTIR-ATR before and after adsorption process was high evidence tools for confirming the adsorption.